The Development of Externalist Semantics. (1st August 2013) - Putnam, Hilary
Abstract: In this lecture I describe the path by which I was led to the "semantic externalism" for which I was honoured with the Rolf Schock Prize. Although my interest in linguistics goes back as far as my undergraduate days, it was conversations with Jerrold Katz and Jerry Fodor at MIT (where all three of us taught at the time) in the 1960s that first led to an effort by all three of us to develop semantic theories. My own direction was a false one, by my present lights; at that time all three of us defended the "internalist" view that the meaning of a word is fixed by a "battery of semantical rules" implicitly known by each speaker. I describe how I was led to the realization that this could not be right, and finally to the views I defended in "The Meaning of 'Meaning' ".